Cave morphology and human-mediated sediment deposition: Late Pleistocene to Holocene evolution of the cave floor at Panga ya Saidi, coastal Kenya - Jennifer M. Miller; Ceri Shipton; Nikos Kourampas; Josep M. Parés; Hubert Vonhof; Mohammad Javad Shoaee; Arturo Cueva-Temprana; Makayla Harding; Alison Crowther; Dovydas Jurkenas; Doreen Mutoro; Jacopo Niccolò Cerassoni; et al. (PLoS ONE, 2026)
Panga ya Saidi (PYS), a cave situated in a forested upland near the coast of Kenya, contains an archaeological record that spans at least 78,000 years and is crucial for understanding the evolution of Homo sapiens populations in eastern Africa. Here we report on new systematic excavation, three-dimensional scanning, radiocarbon dating, and geoarchaeological analyses that provide insights on sedimentary dynamics, occupation patterns, and site-formation processes at PYS. Our data show that while unroofed parts of the cave probably contain the deepest stratigraphies, these are likely to be dominated by colluvial influx and yield limited cultural deposits. Sheltered zones near the chamber edges exhibit better stratigraphic integrity and higher artifact densities, with deposits exceeding 5.5 meters in thickness in the main excavation area. In this area, marked shifts in occupation intensity and sediment sources enable us to reconstruct the evolution of the inhabited cave space. Our findings underscore PYS as a key site for understanding human behavior, adaptation, and environmental interactions from the Late Pleistocene to the Holocene, with implications for broader interpretations of the evolution of Homo sapiens populations in eastern Africa.